Coastal Flood Modeling to Explore Adaptive Coastal Management Scenarios and Land-Use Changes Under Sea Level Rise - Louisor, Jessie; Brivois, Olivier; Mouillon, Paloma; Maspataud, Aurelie; Belz, Patrice; Laloue, Jean-Michel (Frontiers in Marine Science, 2022)
In a Climate Change (CC) context, low-lying areas like marshes are more vulnerable to Sea Level Rise (SLR) or extreme climate events leading to coastal flooding. The main objective of this study is to help local stakeholders determine the best coastal management strategy for the Moëze marsh (France) that can contribute to adapt to SLR in this zone. To do so, we used the MARS hydrodynamic model to simulate coastal overflowing in the zone for different scenarios. We first calibrated the model based on data from the Xynthia storm which occurred on February 28th 2010. Our focus is on modeling the high astronomical tide-induced flooding, taking into account regional SLR projections by 2030 and 2050 under the pessimistic RCP 8.5 CC scenario. Several Coastal management configurations proposed by local decision-makers, as well as different land-use projections were considered. The results highlight that the implementation of closed defenses around human and economic stakes do not lead to significant reductions in flooding (surface extent and maximum water height) compared to the case where the sea-dikes are no longer maintained and the coastline is unconstrained. This can be explained by the fact that these stake zones were historically built on higher points of the marsh. We have also shown that land-use changes have an influence on flooding in the Moëze marsh, especially an increase greater than 0.25 m in the maximum simulated height when considering a new land-use by 2030. The increase is less pronounced (under 0.25 m) when considering a new land-use by 2050. These results do not take into account the possible future evolution of the topography due, for example, to the presence of new habitats that would trap the sediments.